Impact of Surgical Resection of the Primary Tumor on Overall Survival in Patients With Metastatic Pheochromocytoma or Sympathetic Paraganglioma. Issue 1 (July 2018) - Roman-Gonzalez, Alejandro; Zhou, Shouhao; Ayala-Ramirez, Montserrat; Shen, Chan; Waguespack, Steven G.; Habra, Mouhammed A.; Karam, Jose A.; Perrier, Nancy; Wood, Christopher G.; Jimenez, Camilo
Abstract : Objective: To determine whether primary tumor resection in patients with metastatic pheochromocytoma or paraganglioma (PPG) is associated with longer overall survival (OS). Background: Patients with metastatic PPG have poor survival outcomes. The impact of surgical resection of the primary tumor on OS is not known. Methods: We retrospectively studied patients with metastatic PPG treated at the University of Texas, MD Anderson Cancer Center from January 2000 through January 2015. Kaplan-Meier analysis with log-rank tests was used to compare OS among patients undergoing primary tumor resection and patients not treated surgically. Propensity score method was applied to adjust for selection bias using demographic, clinical, biochemical, genetic, imaging, and pathologic information. Results: A total of 113 patients with metastatic PPG were identified. Eighty-nine (79%) patients had surgery and 24 (21%) patients did not. Median OS was longer in patients who had surgery than in patients who did not [148 months, 95% confidence interval (CI) 112.8–183.2 months vs 36 months, 95% CI 27.2–44.8 months; P < 0.001]. Fifty-three (46%) patients had synchronous metastases; of these patients, those who had surgery had longer OS than those who did not (85 months, 95% CI 64.5–105.4 months vs 36 months, 95% CI 29.7–42.3 months; P < 0.001). Patients who had surgery had a similar ECOG performance status to the ones who did not ( P = 0.1798, two sample t test; P = 0.2449, Wilcoxon rank sum test). Univariate and propensity score analysis confirmed that patients treated with surgery had longer OS than those not treated surgically irrespective of age, race, primary tumor size and location, number of metastatic sites, and genetic background (log-rank P < 0.001). In patients with hormonally active tumors (70.8%), the symptoms of catecholamine excess improved after surgery. However, the tumor burden was a more important determinant of OS than hormonal secretion. Conclusions: Primary tumor resection in patients with metastatic PPG appeared to be associated with improved OS. In patients with hormonally active tumors, surgical resection led to better blood pressure control. Abstract : Supplemental Digital Content is available in the text